Penggunaan E-Modul Berbasis Android untuk Meningkatkan Pemahaman Siswa dalam Mata Pelajaran Kimia di SMKN 1 Bonai Darussalam - Masrida, Masrida; Supiarti, Tri (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to analyze the effectiveness of Android-based e-modules in enhancing students’ understanding of Chemistry at SMKN 1 Bonai Darussalam. The research employs Classroom Action Research (CAR), consisting of multiple cycles, including planning, action implementation, observation, and reflection. Data were collected through concept comprehension tests administered before and after using the e-module, classroom observations, and questionnaires measuring students’ responses to this digital learning medium. The findings indicate that using Android-based e-modules significantly improves students’ comprehension of Chemistry concepts compared to conventional teaching methods. Additionally, students demonstrated higher learning interest and more active engagement during the learning process. Data analysis using triangulation techniques confirmed that e-modules not only facilitate access to learning materials but also enhance the overall teaching and learning process. Reflections from each cycle provided insights into optimizing the design and delivery of e-modules to be more interactive and tailored to students’ needs. Thus, this study confirms that the implementation of Android-based e-modules can serve as an innovative solution for improving students’ understanding of Chemistry.